The O28 Antigen Gene Clusters of Salmonella enterica subsp. enterica Serovar Dakar and Serovar Pomona Are Different - Clifford G. Clark; Christopher C. R. Grant; Keri M. Trout-Yakel; Helen Tabor; Lai-King Ng; Kris Rahn; Kristyn Franklin; Andrew M. Kropinski (International Journal of Microbiology)
A 10 kb O-antigen gene cluster was sequenced from a Salmonella enterica subsp. enterica Dakar O28 reference strain and from two S. Pomona serogroup O28 isolates. The two S. Pomona O antigen gene clusters showed only moderate identity with the S. Dakar O28 gene cluster, suggesting that the O antigen oligosaccharides may contain one or more sugars conferring the O28 epitope but may otherwise be different. These novel findings are absolutely critical for the correct interpretation of molecular serotyping assays targeting genes within the O antigen gene clusters of these Salmonella serotypes and suggest the possibility that the O antigen gene clusters of other Salmonella serovars may also be heterogenous.